The Influence of Competence and Work Motivation on Employee Performance After Mutation at PT PLN (PERSERO) UIK SBS - Fitriandi, Tan; Widiyanti, Marlina; Ichsan Hadjri, Muhammad; Yusuf, Muhammad (International Journal Labs, 2024)
Employee performance is crucial for organizational success, particularly in the context of personnel changes such as mutations. At PT PLN (Persero), the effectiveness of employees post-mutation is essential to maintaining operational efficiency and achieving organizational goals. Competence and work motivation are two critical factors that influence how well employees adapt and perform after such changes. Despite the recognized importance of these factors, there is limited empirical research specifically focusing on their impact on employee performance in the context of PT PLN (Persero) UIK SBS.This study aims to determine and analyze the effect of competence and work motivation on employee performance after mutation at PT PLN. This research uses quantitative methods with a population of all PT PLN (Persero) UIK SBS employees in 2023, totalling 149 employees. This study uses a saturated sample method, and data is collected through questionnaires distributed directly through Google Forms. The results showed that both competence and work motivation positively and significantly influence employee performance. These findings emphasize the importance of competency development and increasing work motivation to achieve optimal performance after mutation. This study implies that organizations need to focus on training and development programs that can improve competencies and create a work environment that can motivate employees to achieve better work performance.